1998
DOI: 10.1021/ie9704408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Cellobiose Decomposition in Sub- and Supercritical Water

Abstract: Cellobiose decomposition kinetics and products in sub- and supercritical water were studied with a flow apparatus at temperatures from 300 to 400 °C at pressures from 25 to 40 MPa, and at short residence times (0.04−2 s). Cellobiose was found to decompose via hydrolysis of the glycosidic bond and via pyrolysis of the reducing end. Pyrolysis products were glycosylerythrose (GE) and glycosylglycolaldehyde (GG) which were confirmed by FAB-MS. Hydrolysis products were glucose, erythrose, and glycolaldehyde from ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
142
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 7 publications
(14 reference statements)
10
142
0
Order By: Relevance
“…This is in contrast to the observation of a higher degradation rate for the monomer (kgtot ) 0.45 s -1 ) 31 than for the dimer (k1 + k2 ) 0.16 s -1 ). 13 Second, the hydrolysis rate in the present model is independent of the position of the bond and of the size of the fragment. This is contrary to theoretical arguments 33 and experimental data on acid hydrolysis of xylo-oligosaccharides 14 and R-(1,4)-glucans, 15 which indicate that the glucosidic bond at the nonreducing end should be scissioned about twice as fast as the other bonds.…”
Section: Performance Of the Model And Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This is in contrast to the observation of a higher degradation rate for the monomer (kgtot ) 0.45 s -1 ) 31 than for the dimer (k1 + k2 ) 0.16 s -1 ). 13 Second, the hydrolysis rate in the present model is independent of the position of the bond and of the size of the fragment. This is contrary to theoretical arguments 33 and experimental data on acid hydrolysis of xylo-oligosaccharides 14 and R-(1,4)-glucans, 15 which indicate that the glucosidic bond at the nonreducing end should be scissioned about twice as fast as the other bonds.…”
Section: Performance Of the Model And Discussionmentioning
confidence: 78%
“…Optimization of model parameters indicated that mannan thermal hydrolysis has an activation energy similar to those of recently published results for cellobiose. 13 The activation energy for degradation is higher than that for hydrolysis, which may be related to the influence of the formate buffer. The present model can be applied to first-order depolymerization of other linear polymers with one link type in order to determine reaction rate constants or make predictions about molecular weight distribution on the basis of known reaction rate constants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, though studies have been published on the kinetics of the degradation and hydrolysis of mono-, di-, oligo-, and polysaccharides in subcritical water, 11,12,[15][16][17] application-oriented publications remain the majority. We too have reported several studies on the kinetics of degradation of mono-, 18) di-, [19][20][21] tri-, 22) and oligosaccharides 8) under subcritical conditions.…”
mentioning
confidence: 99%
“…Many researchers have reported the extraction of natural substances from plant sources with subcritical water. [3][4][5][6] Kabyemela et al have investigated the epimerization and decomposition of glucose 7) and the decomposition of cellobiose 8) in sub-and supercritical water. Yoshida et al 9) have reported the production of organic acids and amino acids through the hydrolysis ofˆsh meat by subcritical water.…”
mentioning
confidence: 99%